Puss in boots [videorecording (DVD)] - Miller, Chris, 1975-; Banderas, Antonio; Hayek, Salma, 1966-; Galifianakis, Zach; Thornton, Billy Bob; Sedaris, Amy; Jackman, Henry (Henry Pryce); Perrault, Charles, 1628-1703 (DreamWorks Home Entertainment, 2012)
A story about the events leading up to the sword-fighting cat's meeting with Shrek and his friends.